Emirati Adolescents' and Young Adults' Usage of Social Media for Health Information - Hiba Jawdat Barqawi; Kamel A. Samara; Hanae Qousae Al Chame; Ibrahim Marouf Al Shyyab; Mariam A. Almaazmi (MDPI AG, 2023)
During the COVID-19 pandemic and in the years after, adolescents' and young adults' (AYAs) usage of social media increased. Social media has been shown to influence both the physical and mental behaviour of AYAs. The Emirates' AYAs are among the world's heaviest consumers of social media. This study aims to explore the usage of social media networks by AYAs for sharing and looking up health information, as well as interacting with local health systems, with a special focus on doctors and social media. This cross-sectional, descriptive study was used to collect comprehensive data from Arabic- and English-speaking Emirati students in grades 7 through 12 and university students between the months of December 2022 and April 2023. A total of 876 out of 930 responses were included. Of the responses, 27.71% were university students, with another 46.46% in grades 11 and 12. Three-fourths had a hospital or clinic visit in the last 6 months and 79.11% had good health perception. Smartphones were the most commonly used devices, at 92.12%. A total of 74.7% reported being able to obtain useful health information, with 40% having had a health decision influenced by it. Posting information on social media was not common, with only 32% posting such content (most commonly mood-related). Health information on social media by health authorities was considered the most trustworthy, with celebrities being the least trustworthy. More than half of AYAs searched for a physician before a visit, and the majority would not mind having a rash picture being posted on a public website if consent (verbal or written) was taken. Social media can influence the various health decisions an AYA might take and which doctors they might choose to see. Physicians should consider their presence and the content they present on social media carefully.